Research on Animation VR System Scenario Considering High-Precision Line of Sight Tracking Algorithm (Informatica, 2024)
At present, the utilization of eye tracking tech in the context analysis of the animation VR system can provide the best line of sight effect from the current perspective draw support from the detection of the viewer's eye movement position, make the VR animation context more natural, have a higher sense of immersion, and greatly strengthen the interaction of the system. On account of this, this paper first analyzes the theoretical basis of line of sight tracking tech represented by particle filter mechanism, and then studies the high-precision line of sight tracking algorithm of self-organizing fusion of single feature, single target and multi line of sight features, as well as the performance and performance amelioration strategies of different algorithms. Finally, this paper presents the implementation of animation VR situation considering high-precision line of sight tracking algorithm.